Differential effects of clopidogrel and/or aspirin on the healing of tooth extraction wound bone tissue - Wang, Jiaping; Lin, Juan; Song, Xin; Wang, Mengting; Chen, Yan; Luo, Ning; Wu, Xin (Frontiers in Physiology, 2024)
(1)Background: A multitude of variables influence the healing of tooth extraction wounds, and delayed extraction wounds might complicate later prosthodontic therapy. In this research, we analyzed the effects of systemic clopidogrel and aspirin alone or in combination on the healing of tooth extraction wounds in mice. (2)Methods:ICR mice were randomly divided into four groups: control group , clopidogrel group, aspirin group, and clopidogrel combined with aspirin group; left upper first molar was extracted ,CLOP/ASP/CLOP+ASP groups were respectively administered with clopidogrel, aspirin, clopidogre+aspirin, and the control group was given 0.9% saline by gavage. Mice in each group were euthanized at 14 and 28 days postoperatively, and the maxilla was extracted. The tissues in the extraction sockets were examined using MicroCT and sectioned for HE staining, Masson staining, and TRAP staining, and immunohistochemistry staining (for TRAP, RANKL and OPG). (3)Results: MicroCT analysis showed that at day 14, BS/BV was significantly lower in CLOP and CLOP+ASP groups compared to control and ASP groups, while BV/TV, Tb.Th was significantly higher. At day 28, BV/TV was significantly higher in the CLOP+ASP group compared to the CLOP group, with P<0.05 for all results. In the quantitative analysis of Masson, the fraction of newly formed collagen was significantly higher in the CLOP group in comparison with that in the CON group (P<0.05). At day 14, the ASP group had substantially more TRAP-positive cells than the CLOP and CLOP+ASP groups (P<0.05). In immunohistochemical staining, RANKL expression was found to be significantly higher in the ASP group than those in the other three groups at day 28 (P<0.05); OPG expression was significantly higher in the CLOP group and the CLOP+ASP group compared with that at day 14, and was higher than that in the ASP group at day 14 and day 28. OPG/RANKL was significantly higher in the CLOP and the CLOP+ASP groups than in the ASP group (P< 0.05). (4)Conclusion: Clopidogrel alone promotes osteogenesis in the extraction wound, whereas aspirin alone inhibits alveolar bone healing. When the two drugs were combined, the healing effect of the extraction wound was more similar to that of the clopidogrel alone group.